Modelling oxygen transport and tissue damage in the human brain - Xue, Y (2022)
Healthy brain function depends on continuous blood flow carrying oxygen and metabolites. Ischaemic stroke, caused by an occlusion in the cerebral artery that disrupts blood and oxygen supply and leads to irreversible tissue damage, is one of the leading causes of death and disability in the world.